ANALISIS HUBUNGAN FAKTOR DEMOGRAFI DENGAN KUNJUNGAN ANTENATAL CARE PADA IBU HAMIL TRIMESTER III - Gustini, Gustini; Sibua, Siska; Kamaruddin, Mustamir; Muzayyana, Muzayyana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Pregnancy is a very vulnerable period that requires special attention, not only for pregnant women, but also for the safety of the fetus. Based on the results of a preliminary survey conducted in the working area of the Sababilah Community Health Center, it was found that the coverage of pregnancy visits, both Pregnant Women Visits (KI) and Fourth Visits (K4), was still very low. The purpose of this study was to analyze the relationship between demographic factors and antenatal care visits in pregnant women in their third trimester. A cross-sectional study design was used in this study. The study was conducted in Sababilah in October 2024. The population consisted of all pregnant women in their third trimester who had made their sixth visit. The sample consisted of 30 respondents. The sampling technique used total sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between occupation (p value: 0.04) and education (p value: 0.00) and ANC visits. Health workers and cadres are advised to further enhance promotion and education programs for pregnant women regarding the importance of attending antenatal care visits. Pregnant women should be encouraged to be more motivated and caring towards their pregnancies, adopt positive health behaviors, and be more active in participating in health services, especially antenatal care visits. Keywords: Antenala Care, Work, Education